Analysis of the impact of banking sector credit on the real sector - Magaji, Sule; Musa, Ibrahim (Asian Journal of Economics and Empirical Research, 2023)
This study examines the impact of banking sector credit on Nigeria’s real sector based on data from 1986 to 2019 using the ARDL model. The bound testing result indicates that there is a long-run relationship between the variables of interest with real gross domestic product (RGDP) as the dependent variable. The result indicates that commercial bank credit (CBC) has a positive impact on RGDP in the long and short runs, which is consistent with a priori expectations. Domestic private investment (DPI) was found to have a negative and significant relationship with RGDP in the long and short runs. The estimated equations of the specified models show a significant positive relationship between government capital expenditure (GCE) and RGDP. In the short run, a significant increase in DPI, CBC, and GCE will bring about a significant increase in RGDP. The parameter estimates of DPI, CBC and GCE are statistically significant, as indicated by the t-value. The study reveals that effective utilization and distribution of bank credit to the real sector promotes economic growth. Therefore, the study recommends that there should be improved banking sector credit which will improve the output of the real sector and, in turn, boosts the economy.